2005
DOI: 10.1007/s11242-004-5738-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a CT-Scanned Counter-Current Flow Experiment

Abstract: Counter-current flow occurs in many reservoir processes and it is important to understand and model these processes in order to operate them effectively. Both drainage and imbibition processes exist simultaneously during counter-current flow. It has thus proven difficult to model this type of flow using conventional techniques because of the impossibility of assigning a single capillary pressure curve applicable over the entire sample. In the current paper, a new saturation-history-dependent approach has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The relative permeability and capillary pressure curves were extracted from the experimental data using an automated-history-matching method and with the aid of a commercial reservoir simulator (Eclipse ). Li et al (2005) also demonstrated that counter-current flow could be modeled with a single capillary pressure curve and one pair of relative permeability curves only if fluid banks did not form. When fluid banks formed, the saturation history-dependent method must be implemented.…”
Section: History-dependent Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative permeability and capillary pressure curves were extracted from the experimental data using an automated-history-matching method and with the aid of a commercial reservoir simulator (Eclipse ). Li et al (2005) also demonstrated that counter-current flow could be modeled with a single capillary pressure curve and one pair of relative permeability curves only if fluid banks did not form. When fluid banks formed, the saturation history-dependent method must be implemented.…”
Section: History-dependent Modelingmentioning
confidence: 99%
“…A history-dependent model developed by Li et al (2005) was used to simulate the experimental data. Li et al's (2005) model uses two pairs of relative permeability curves (drainage and imbibition) and the bounding capillary pressure curves of the capillary hysteresis loop to reproduce counter-current flow experiments.…”
Section: History-dependent Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to correctly model oil recovery processes, capillary pressure hysteresis has to be taken into consideration with a specified saturation history for each gridblock. The development of such a model, called history-dependent modeling, is given by Li et al (2005). In this modeling method, different capillary pressure (scanning) curves are assigned to different locations according to the initial saturation and saturation history, and different relative permeability curves are assigned to the different flow regimes.…”
Section: Hysteresis Of Parameters Controlling Counter-current Flowmentioning
confidence: 99%
“…Comparing with NMR, it will cost less money for CT scanning while ensuring study result. From the 1980s onwards, petroleum engineers began to use CT technology in core analysis to determine porosity, internal structure, and the change of fluid saturation in the course of displacement (Walsh and Withjack 1994;Schembre and Kovscek 2003;Li et al 2005;Du et al 2007).…”
mentioning
confidence: 99%